Role of Endoscopic Biliary Stenting in the Management of Difficult Common Bile Duct Stones - Nimai Das; Chinmoy Saha; Shishir Sikto Sarker; Dr Tasmia Tanjum; Sanghita Ghose; Chanchal Kumar Ghosh (Journal of Healthcare and Biomedical Science, 2025)
Removing large or multiple common bile duct stones that cannot be cleared at first endoscopic retrograde cholangiopancreatography (ERCP) is difficult in resource-limited settings. This study assessed whether temporary plastic stenting promotes subsequent clearance of these “difficult” stones. In a prospective observational study at Bangabandhu Sheikh Mujib Medical University, Dhaka (November 2019 – March 2021), 35 adults with difficult common bile duct stones underwent endoscopic sphincterotomy followed by placement of a 7–10 Fr plastic stent. Stone size, number, index, and duct diameter were measured before stenting and at repeat ERCP three months later. Clearance rates and stent-related adverse events were recorded. Thirty-one patients completed follow-up. Mean stone size fell from 19.1 ± 2.1 mm to 15.8 ± 3.1 mm; mean stone number from 1.80 ± 0.74 to 1.45 ± 0.67; and mean stone index from 28.9 ± 9.2 mm to 20.9 ± 9.9 mm (all p < 0.001). Complete bile duct clearance at second-session ERCP was achieved in 69.7%, while 6.1% showed spontaneous passage. Complications were limited to stent migration (6%), occlusion (9%), and cholangitis (6%), with no procedure-related mortality. Short-term endoscopic biliary stenting safely reduces stone burden and enables successful second-session extraction in most patients with difficult common bile duct stones. It offers an effective bridge therapy where advanced lithotripsy techniques are unavailable.